The Poverty of Anti-economicist liberalism: the cases of Barros and Merquior - Barbieri, Fabio (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2022)
This article examines, compares and criticizes two books on the history of classical liberalism, written by written by two Brazilian intellectuals, Roque Spencer Maciel de Barros and José Guilherme Merquior. These works are used as case studies of the consequences of reducing politics to morals. We argue that, by rejecting the contributions of economists to liberalism, the two authors offer emptied versions of liberalism, as they ignore crucial elements of liberal doctrine, namely, the study of the unintended consequences of human action and the fallibilist model on the growth of knowledge.